The added gradient echo pulse sequence technique: application to imaging of fluid in the temporomandibular joint. - Bell, K A; Jones, J P; Miller, K D; al-Refal, D (American Journal of Neuroradiology, 1993)
PURPOSE To assess the value of an added gradient echo in the same pulse sequence with a T1-weighted spin echo for determining the presence of an abnormal fluid collection in the temporomandibular joint with no additional imaging time.MATERIALS AND METHODS Using a standard T1-weighted sequence used in cine temporomandibular joint imaging, a readout gradient reversal was added and the resulting gradient echo collected. This image was compared with standard T1- and T2-weighted sequences, a short inversion recovery imaging sequence, and a small flip angle fast low-angle shot gradient-echo sequence.RESULTS The T1-weighted spin echo preceding the added gradient echo is not affected by the gradient reversal, but the additional gradient echo adds T2* contrast information that displays fluid as bright as and compares favorably with other fluid detection sequences.CONCLUSION The added gradient-echo technique adds sensitivity for the detection of an abnormal increase in fluid in the temporomandibular joint without adding to the overall imaging time of a routine T1-weighted sequence.